A Highly Conserved Enhancer in the Dlx5/Dlx6Intergenic Region is the Site of Cross-Regulatory Interactions betweenDlx Genes in the Embryonic Forebrain - Zerucha, Ted (J Neurosci, 2000)
Four Dlx homeobox genes, Dlx1,Dlx2, Dlx5, and Dlx6 are expressed in the same primordia of the mouse forebrain with temporally overlapping patterns. The four genes are organized as two tail-to-tail pairs, Dlx1/Dlx2 and Dlx5/Dlx6, a genomic arrangement conserved in distantly related vertebrates like zebrafish. The Dlx5/Dlx6 intergenic region contains two sequences of a few hundred base pairs, remarkably well conserved between mouse and zebrafish. Reporter transgenes containing these two sequences are expressed in the forebrain of transgenic mice and zebrafish with patterns highly similar to endogenous Dlx5 andDlx6 expression. The activity of the transgene is drastically reduced in mouse mutants lacking both Dlx1and Dlx2, consistent with the decrease in endogenousDlx5 and Dlx6 expression. These results suggest that cross-regulation by Dlx proteins, mediated by the intergenic sequences, is essential for Dlx5 andDlx6 expression in the forebrain. This hypothesis is supported by cotransfection and DNA-protein binding experiments. We propose that the Dlx genes are part of a highly conserved developmental pathway that regulates forebrain development.